The Influence of Learning Independence on Student Learning Outcomes in Economics Subjects Class XI IPS SMAN 2 Mandau - Tommy, Yakub; Syahza, Almasdi; Rizka, Mifta (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the effect of independent learning on student learning outcomes in economics subjects at SMA N 2 Mandau. The method used in this research is descriptive quantitative, with a respondent population of 172 students and a sample of 64 students obtained from sampling using random sampling techniques who were chosen at random. The data collection instrument used in this research was a questionnaire in the form of a list of questions using a Likert scale. The independent variable in this research is learning independence and the analysis technique used is simple linear regression. The research results obtained show that learning independence significantly and partially influences student learning outcomes. This is based on the results of the t test calculation of the learning independence variable which obtained a tcount of 9.177 with a ttable value of 1.998. So it can be concluded that based on the results of the t test and supported by the results of the descriptive test, the learning independence variable influences student learning outcomes with a contribution of 56.9% and the remaining 42.4% is influenced by variables that were not examined.